2009
DOI: 10.1103/physrevlett.102.107004
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Transition at 38 K in Insulating-OverdopedLa2CuO4La1.64Sr0.36CuO

Abstract: We use resonant soft x-ray scattering (RSXS) to quantify the hole distribution in a superlattice of insulating La2CuO4 (LCO) and overdoped La2-xSrxCuO4 (LSCO). Despite its nonsuperconducting constituents, this structure is superconducting with T_{c}=38 K. We found that the conducting holes redistribute electronically from LSCO to the LCO layers. The LCO layers were found to be optimally doped, suggesting they are the main drivers of superconductivity. Our results demonstrate the utility of RSXS for separating … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 18 publications
7
83
1
1
Order By: Relevance
“…Charge transfer between the different unit cells allows superconductivity to be explained [82]. Exposed to an ozone atmosphere, T c is boosted to 50 K, a value that is not reached in single-phase films.…”
Section: High T C Heterostructuresmentioning
confidence: 99%
“…Charge transfer between the different unit cells allows superconductivity to be explained [82]. Exposed to an ozone atmosphere, T c is boosted to 50 K, a value that is not reached in single-phase films.…”
Section: High T C Heterostructuresmentioning
confidence: 99%
“…Further, the induced changes in the carrier concentration are limited to an extremely thin layer at the surface of the sample. The thickness of this active layer is determined by the Thomas-Fermi screening length, which along the c-axis in LSCO has been determined to be of 6 Å , 17 i.e., about the thickness of 0.5 UC (one molecular layer) of LSCO. Thus, essentially only the topmost CuO 2 layer can be significantly modified and the effect should vanish in the bulk.…”
Section: Resultsmentioning
confidence: 99%
“…1(a)). [15][16][17][18] Since the electrostatic screening length for cuprates is of the order of one unit cell, it is imperative that the deposited films are continuous and defect-free on the same length scale. The crystal structure of films was monitored in situ during growth by reflection high energy electron diffraction (RHEED) and after growth studied by x-ray diffraction.…”
Section: Methodsmentioning
confidence: 99%
“…In 2003, it was shown by Bozovic et al [4] that no charge redistribution occurs between La 1.85 Sr 0.15 CuO 4 and La 2 CuO 4 . The measurement in M-I bilayers was performed by Smadici et al [5] using a novel synchrotron-based technique, resonant soft X-ray scattering. They measured a superlattice that consisted of 15 periods, each containing 1 UC of I and 2 UC of M. Again, none of the constituents were superconducting but the superlattice showed T c ≈ 38 K. The analysis of the data showed that the holes were not bound to the Sr 2+ ions; they redistributed between the layers, generating a carrier concentration of about 0.15 holes/Cu in the middle of La 2 CO 4 layers.…”
Section: Interface Superconductivitymentioning
confidence: 99%